EFFICACY OF PLEUROTUS SAJOR CAJU AS AN EXCELLENT POTTING MEDIUM FOR GARDEN PLANTS - P. B .HARATHI,; R.RADHA,; M. GAYATHRI, (International Journal of Pharma and Bio Sciences, 2016)
Coir is a natural fibre found between the hard, internal shell and the outer coat of a coconut is used as a by-product of the coir manufacturing industry. Normally, they are dumped as agricultural wastes in the fields or disposed by burning which causes air pollution. Composting of coir pith is an alternate method to reduce pollution and it also serves as a source for the maintenance of organic matter of the soil. Coir pith is an ideal soil re-conditioner and soil substrate with excellent water holding capacity. Coir pith contains high quality of nutrients which keeps the soil healthy in a natural way. It acts as a top dressing that helps to maintain moisture content of the soil and re-conditions the soil. The proportion yielded effective growth of the plant and indicating its use as an excellent potting media for garden plants. Hence the objective of the present study focused on the efficacy of basidiomycetes fungus, Pleurotus sajor-caju for the cultivation of medicinal plant, Ocimum santum using the biodegraded coir pith.